Foreign aid and international assistance for implementing free basic education in sub - saharan Africa: prospects and challenges (2017)
The paper analyses the trends of aid to education in Sub Saharan Africa. It examines the obligations under international human rights instruments that poor states should seek assistance from richer nations. References to ‘international assistance cooperation’ in article2.1 and to ‘international action’ in article 23 of the ICESCR are of particular relevance for poor States. Where a State party is clearly lacking in the financial resources and/ or expertise required to provide free education for its children, the international community has a clear obligation to assist under international human rights laws. It is revealed that Sub Saharan Africa receives a declining share to basic education, therefore aid to basic education must be better allocated and sufficiently in Sub-Saharan Africa. So the question was raised that what should be done? The answer as discussed in the paper is threefold; first, there is a need to increase the amounts of aid provided. Second aid should be based more firmly on both needs and the capacity to absorb the aid provided in a transparent manner by demanding greater accountability and transparency in terms of the allocation and use of aid funds. Finally it is important to ensure that the aid supplied will be provided for a sufficient length of time for it to have a better chance of making a difference by working to ensure better outcome in availability and accessibility to education for children in Africa and to reach Sustainable Development Goal 4 (SDG 4)